Harmful occupational factors of shoe productions: noise and vibration. - U. B. Lototska-Dudyk (Medičnì Perspektivi)
Shoe production is an important and promising industry of light industry in Ukraine. More than 15 thousand people work at almost 300 enterprises. Improvement of technologies and equipment, intensification of production processes on the background of their incomplete mechanization and automation cause production noise and vibration at the workplaces, in particular, in сutting, сlicking and closing workshops. Levels of manufacturing noise and production vibration in the workplaces of workers of the main occupations: cutters, clicking details, shoe markers, seamstresses, striking operatives, сementing operators, fitters and lasters, trimers and bottom scourers were analyzed. According to noise level, working conditions of cutters on the сutting machines Gerber, seamstresses, skivers, stitchers of upper, casters, fitters and lasters, сementing operators belong to the 2nd class (permissible). The working conditions of cutters on the сutting presses, shoe markers, fitters of upper on the heavy-class sewing machines, bottom scourers, trimers and striking operatives are classified as harmful ones (class 3.1), on separate workplaces of clicking details (press PVH-8) and bottom scourers – class 3.2 degree of danger. Equivalent correction levels of local and general vibration don’t exceed permissible levels. The presence of related unfavorable industrial factors necessitates the study of both combined and jointed action of noise and vibration with the subsequent assessment of the risks to the health of workers in the light industry.